2015
DOI: 10.2147/ndt.s74905
|View full text |Cite
|
Sign up to set email alerts
|

Perfectionism related to self-reported insomnia severity, but not when controlled for stress and emotion regulation

Abstract: BackgroundPerfectionism is understood as a set of personality traits such as unrealistically high and rigid standards for performance, fear of failure, and excessive self-criticism. Previous studies showed a direct association between increased perfectionism and poor sleep, though without taking into account possible mediating factors. Here, we tested the hypothesis that perfectionism was directly associated with poor sleep, and that this association collapsed, if mediating factors such as stress and poor emot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
52
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 55 publications
(56 citation statements)
references
References 37 publications
4
52
0
Order By: Relevance
“…14 With regard to subjective parameters of sleep, studies found that perfectionism is associated with sleep onset latency (SOL) 10,14,16 and wake after sleep onset (WASO). 14,16 Studies on perfectionism and sleep have relied on selfreported measures of sleep, and it has not been investigated whether higher levels of perfectionism are also linked to poor sleep as measured by polysomnography (PSG).…”
Section: Journal Of Clinical Sleepmentioning
confidence: 99%
See 4 more Smart Citations
“…14 With regard to subjective parameters of sleep, studies found that perfectionism is associated with sleep onset latency (SOL) 10,14,16 and wake after sleep onset (WASO). 14,16 Studies on perfectionism and sleep have relied on selfreported measures of sleep, and it has not been investigated whether higher levels of perfectionism are also linked to poor sleep as measured by polysomnography (PSG).…”
Section: Journal Of Clinical Sleepmentioning
confidence: 99%
“…[11][12][13] Longitudinal studies suggest that perfectionism is indeed a risk factor for insomnia symptoms. 14,15 Further findings have shown that the link between insomnia symptoms and perfectionism may be mediated by emotional distress, 15 stress perception, and emotion regulation 16 or anxiety. 17 Perfectionism is often assessed using the Hewitt and Flett Multidimensional Perfectionism Scale (MPS) 18 or the Frost Multidimensional Perfectionism Scale (FMPS).…”
Section: Introductionmentioning
confidence: 98%
See 3 more Smart Citations